(untitled) (Majalah Kedokteran Bandung, 2022)
The high incidence of breast cancer cases in the world requires the use of applicative methods. The 7,12-dimethylbenz(a)anthracene (DMBA) induced breast cancer animal model is a widely used chemical-induced animal models for research on breast cancer. However, the molecular mechanism related to DMBA induction remains unclear. Good understanding on DMBA-induced animal models is crucial for studies related to future breast cancer treatments as animal models will provide a deeper understanding of anticancer medication, specifically those aimed for treating breast cancer. The aim of this study was to develop an DMBA-induced animal model for breast cancer. This study used female Wistar rats injected subcutaneously with DMBA as a carcinogen-induced agent (20 mg/kg) to induce tumor. Rat tumors were then evaluated and breast appearance was observed weekly, starting from day 28th after DMBA injection. Breast cancer tissue was then sampled and stored at -80°C until it was used for western blot and histological study. This study indicated that DMBA induced cancer in female Wistar rat’s breasts, and cytoplastic cells and lung metastatic was identified macroscopically and histopathologically. The metabolic sign was observed in the lung and breast sections. Interestingly, the DMBA induction in this study does not only induce organ cancers but also induces estrogen receptors and stimulates signaling of estrogen receptors Î± (ERÎ±), ERÎ², and Akt.